TAFSIR AYAT-AYAT JUAL BELI DALAM PERSPEKTIF EKONOMI SYARIAH MODERN - Angriani, Yupita; Putri, Rafiqa Edyan; Rohimin, Rohimin; Ramadlon, Abah (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
This study aims to examine the interpretation of the verses of the Qur'an related to buying and selling transactions, as well as their relevance in the perspective of modern Islamic economics. Buying and selling in Islam does not only include the exchange of goods or services, but also includes moral and ethical principles that must be followed so that transactions run fairly, transparently, and free from detrimental practices such as usury, gharar (uncertainty), and maysir (gambling). This study uses a thematic interpretation approach to analyze the verses that discuss buying and selling, such as those found in Surah Al-Baqarah (2:275-279), Surah An-Nisa' (4:29), and Surah Al-Mumtahanah (60:8). The results of this study indicate that the application of the principles taught in the Qur'an, such as the prohibition of usury, clarity in transactions, and avoidance of speculation, is very relevant in modern Islamic economics. This research is expected to contribute to developing a more just and sustainable economic system.